Prostate cancer in Asia: A collaborative report - Chen, Rui; Ren, Shancheng; Yiu, Ming Kwong; Fai, Ng Chi; Cheng, Wai Sam; Ian, Lap Hong; Naito, Seiji; Matsuda, Tadashi; Kehinde, Elijah; Kural, Ali; Chiu, Jason Yichun; Umbas, Rainy; et al. (ELSEVIER SINGAPORE PTE LTD, 2014)
The incidence of prostate cancer (PCa) within Asian population used to be much lower than in the Western population

however, in recent years the incidence and mortality rate of PCa in some Asian countries have grown rapidly. This collaborative report summarized the latest epidemiology information, risk factors, and racial differences in PCa diagnosis, current status and new trends in surgery management and novel agents for castration-resistant prostate cancer. We believe such information would be helpful in clinical decision making for urologists and oncologists, health-care ministries and medical researchers. (C) 2014 Editorial Office of Asian Journal of Urology. Production and hosting by Elsevier (Singapore) Pte Ltd.
Keywords: Prostate cancer; Asian population; Epidemiology; Risk factors; Racial differences; Surgery management